PENGETAHUAN MASYARAKAT MENGENAI PROSEDUR MEDIASI DI PENGADILAN - Gomgom TP Siregar; Syawal Amry Siregar; Muhammad Yasid (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2021)
Mediation is a way of resolving disputes through a third party, commonly known as a mediator. The mediator with his capacity as a neutral party seeks to reconcile the parties by providing advice on dispute resolution. Proposals for dispute resolution through mediation are made rather informal. Dispute resolution through mediation is not binding. Mediation prioritizes a win-win solution without either a winning party or a losing party. In the event that the mediation is conducted in the court building, the mediator under the authority of the Case Examining Judge through the clerk shall summon the parties with the assistance of a bailiff or substitute bailiff to attend the mediation meeting. The mediation process lasts a maximum of 30 (thirty) days from the date of the order to mediate. The problem faced by the target audience before giving the material was the lack of knowledge of the people of Hilinifaoso Village, Kec. Ulususua Kab. South Nias regarding mediation procedures in court. The implementation of this community service activity can be said to have been successfully implemented and the benefits can be felt directly by the participants, namely increasing the knowledge of the people of Hilinifaoso Village, Kec. Ulususua Kab. South Nias regarding mediation procedures in court. This can be seen from the answers of the participants to the questionnaire given after the activity. Of the 31 participants, 95% answered that they understood it.